Shear Bond Strength of Ceramic Bonded to Different Core Materials and Their Pattern of Failure: An In Vitro Study - P, Shilpa (Cureus, 2019)
Introduction In metal-ceramic restoration, most of the bond failures between the ceramic layer and the metal coping is the chipping of the ceramic layer, thus exposing the metal surface, which compromises the aesthetics. Hence, this leads to the introduction of zirconia-based restorations in dentistry. However, even zirconium coping has the common complication of delamination or porcelain chipping from the zirconium core. Hence, the shear bond strength between the commonly used core materials and ceramic requires investigation to facilitate the materials in clinical use for longevity. Therefore, this study was conducted to compare the shear bond strength between different core materials and ceramic layering to find out the best core material for ceramic bonding. Materials and methods A total number of 45 samples were made as per ISO standardization (base 5 mm diameter and 1 mm thickness, step with 4 mm diameter and 4 mm in length). These samples were divided into three groups, Group A: Nickel-chromium, Group B: Cobalt-chromium, and Group C: Zirconium. Ceramic layering was layered on the top surface of each sample until an ideal height of 4 mm was obtained, and it was subjected to shear bond strength using a universal testing machine with a 50-KN load cell. This was followed by analyzing the nature of the fracture pattern using scanning electron microscopy (SEM). Results  There were no significant differences found for the shear bond strength among group A and group B. The zirconium (group C), however, had significantly lower values than both group A and group B. The microscopic examination also revealed that the failure between the coping and the ceramic layer primarily occurred near the interface with the residual veneering porcelain remaining on the core. Conclusions It was found that the shear bond strength of the metal-ceramic group is better than the zirconium ceramic group, however, the fracture between the copings and the ceramic layering is found to be similar for both adhesive and cohesive failure.